2019
DOI: 10.1016/j.cmet.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

A Neuronal Relay Mediates a Nutrient Responsive Gut/Fat Body Axis Regulating Energy Homeostasis in Adult Drosophila

Abstract: SummaryThe control of systemic metabolic homeostasis involves complex inter-tissue programs that coordinate energy production, storage, and consumption, to maintain organismal fitness upon environmental challenges. The mechanisms driving such programs are largely unknown. Here, we show that enteroendocrine cells in the adult Drosophila intestine respond to nutrients by secreting the hormone Bursicon α, which signals via its neuronal receptor DLgr2. Bursicon α/DLgr2 regulate energy metabolism through a neuronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
118
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(119 citation statements)
references
References 87 publications
0
118
0
Order By: Relevance
“…Because we can only detect on average 1,350 genes per cell, it remains possible that hormones with very low expression levels or whose expression is conditional could be missed from our analysis. For example, Bursicon is not detected in our analysis despite it reported to be expressed in some EEs in the posterior midgut (Chen et al, 2016a;Scopelliti et al, 2019). Interestingly, its expression can only be detected by antibody staining but not by mRNA using in situ hybridization (Chen et al, 2016a), suggesting that the transcriptional activity of Bursicon is extremely low but its protein product might be relatively stable.…”
Section: Peptide Hormone Signatures For Each Ee Clustermentioning
confidence: 64%
“…Because we can only detect on average 1,350 genes per cell, it remains possible that hormones with very low expression levels or whose expression is conditional could be missed from our analysis. For example, Bursicon is not detected in our analysis despite it reported to be expressed in some EEs in the posterior midgut (Chen et al, 2016a;Scopelliti et al, 2019). Interestingly, its expression can only be detected by antibody staining but not by mRNA using in situ hybridization (Chen et al, 2016a), suggesting that the transcriptional activity of Bursicon is extremely low but its protein product might be relatively stable.…”
Section: Peptide Hormone Signatures For Each Ee Clustermentioning
confidence: 64%
“…ETH also impairs courtship shortterm memory via its action on JH production [522]. Recent work has shown that bursicon (burs alpha), but not burs beta is expressed in the midgut enteroendocrine cells of Drosophila [264,523]. Interestingly, burs alpha released from these cells activates its receptor, DLGR2, in the gut visceral muscles (VM) to regulate intestinal stem cell quiescence through VM-derived EGF-like growth factor Vein [523].…”
mentioning
confidence: 99%
“…Consequently, burs alpha is released into the hemolymph following sucrose consumption, after which it activates DLGR2 in the CNS to alter systemic metabolic homeostasis through downregulation of AKH signaling [264].…”
mentioning
confidence: 99%
“…On the other hand, transcriptomic analyses showed an enrichment of trypsins in male adults (figure 3.c). The upregulation of allatostatin (Hergarden, Tayler, and Anderson 2012) and the downregulation of CCAP (Žitnan and Daubnerová 2016) and bursicon (Scopelliti et al 2019) allow the male to reduce its food uptake. Taken together, this information supports a self-digestion of extracellular proteins in males driven by eLDPs and trypsin complexes that could act on proteolysis specificity modulation and/or on targeting/protecting specific extracellular proteins.…”
Section: Discussionmentioning
confidence: 99%